Can the New Keynesian Phillips Curve explain inflation gap persistence? - Fang Yao (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
Whelan (2007) found that the generalized Calvo-sticky-price model fails to replicate a typical feature of the empirical reduced-form Phillips curve - the positive dependence of inflation on its own lags. In this paper, I show hat it is the 4-period-Taylor-contract hazard function he chose that gives rise to this result. In contrast, an empirically-based aggregate price reset hazard function can generate simulated data that are consistent with inflation gap persistence found in US CPI data. I conclude that a non-constant price reset hazard plays a crucial role for generating realistic inflation dynamics.
Keywords: E12; E31; 330; Inflation gap persistence; Trend inflation; New Keynesian Phillips curve; Hazard function; New-Keynesian Phillips Curve; Inflationsrate; Preisrigidität; Statistische Bestandsanalyse; Schätzung; Lebenshaltungsindex; USA